Widening access to un dergraduate physiotherapy education in South Africa - pointers from students' records - S.L. Amosun; S. Maart; G. Ferguson; S. Manie (AOSIS, 2012)
In response to the state mandate to improve access and equityin higher education, the admission policy of universities in South Africa (SA)currently employs measures for the redress of past inequalities and racialinjustices. As there is no information on the processes to widen access toundergraduate physiotherapy education program in SA, the aim of this reportedstudy was to search for pointers from students' records in one local university,situated in the Western Province of SA, that would inform the development ofstrategies that will widen the access for previously disadvantaged populationgroups and ensure successful academic outcomes. The records of six cohorts of students who earlier applied for andlater enrolled in the undergraduate physiotherapy program between the years 2000 and 2005 were retrospectivelyreviewed. Information pertaining to access, student characteristics, and academic persistence was extracted, reviewedand analysed descriptively. During the period reviewed, approximately equal numbers of Black and non-Black studentsapplied for admission to the program. The proportion of Black applicants meeting minimum admission requirementswas less than half of the White/Asian applicants. Less than 50% (105/212) of the offers made to Black applicantswere accepted. Forty one percent (43/105) of the enrolled Black students successfully completed the program withinthe minimum 4 years compared to 75.5% (145/192) of the White/Asian students. Strategies should be implementedto increase awareness and recruitment, improve enrolment rates, and improve retention and throughput for Blackstudents in the undergraduate physiotherapy program of a historically "white" SA university.